A single mating is sufficient to induce persistent reduction of immune defense in mated female Drosophila melanogaster. (July 2022) - Gordon, Kathleen E.; Wolfner, Mariana F.; Lazzaro, Brian P.
Graphical abstract: Highlights: Female D. melanogaster are more susceptible to bacterial infection after mating, due to seminal fluid proteins. Female D. melanogaster remain more susceptible to infection for at least 10 days after mating. A second mating event does not compound the suppression of female immune defense. Mating triggers a binary switch in female immune defense to persistently suppress immunity. Abstract: In many species, female reproductive investment comes at a cost to immunity and resistance to infection. Mated Drosophila melanogaster females are more susceptible to bacterial infection than unmated females. Transfer of the male seminal fluid protein Sex Peptide reduces female post-mating immune defense. Sex Peptide is known to cause both short- and long-term changes to female physiology and behavior. While previous studies showed that females were less resistant to bacterial infection as soon as 2.5 h and as long as 26.5 h after mating, it is unknown whether this is a binary switch from mated to unmated state or whether females can recover to unmated levels of immunity. It is additionally unknown whether repeated mating causes progressive reduction in defense capacity. We compared the immune defense of mated females when infected at 2, 4, 7, or 10 days after mating to that of unmated females and saw no recovery of immune capacity regardless of the length of time between mating and infection. Because D. melanogaster females can mate multiply, we additionally tested whether a second mating, and therefore a second transfer of seminal fluids, caused deeper reduction in immune performance. We found that females mated either once or twice before infection survived at equal proportions, both with significantly lower probability than unmated females. We conclude that a single mating event is sufficient to persistently suppress the female immune system. Interestingly, we observed that induced levels of expression of genes encoding antimicrobial peptides (AMPs) decreased with age in both experiments, partially obscuring the effects of mating. Collectively, the data indicate that being reproductively active versus reproductively inactive are alternative binary states with respect to female D. melanogaster immunity. The establishment of a suppressed immune status in reproductively active females can inform our understanding of the regulation of immune defense and the mechanisms of physiological trade-offs.